High‐Resolution Ultrasonic Visualization of the Micromechanical Behavior of Reinforced Composites with Fine Fiber Microstructure. Issue 1 (21st August 2022) - Morokov, Egor; Levin, Vadim
Abstract: In the work, the first results of in situ ultrasound observation of microstructure changes in the volume of carbon fiber reinforced composites under tension are presented. The results depict the mechanical behavior of the laminate with stacking sequences of [−45°/0°/+45°/90°/+45°/0°/−45°]. Ultrasound visualization of volume microstructure is carried out with a controlled stepwise increase in deformation of the loaded specimens. Data of ultrasound investigation are compared with optical microphotograph and strain–stress curves of controlled and tested specimens. This approach makes it possible to visualize in dynamics the processes of appearance, growth, and transformation of microstructural damages in the volume with a resolution of tenth microns.